Análise exploratória dos impactos das decisões de marketing no desempenho de entrega e na flexibilidade da área de operações em uma manufatura de alimentos - Finger, Marcos Eduardo (Universidade do Vale do Rio dos Sinos, 2017)
Improving the performance of manufacturing companies has become a constant challenge in the face of the difficulties of the economic scenario in Brazil and global competitiveness. Thus, the alignment between market demand and the processes and resources required to meet it, is a condition for increasing the competition capacity. In that sense, the marketing and operations areas work together to make this practice a reality. However, studies that explore the objective relationships between these functional areas in low-tech companies, such as food manufacturing, are scarce in the literature. The evaluation of the relations of the marketing and operations areas is an important tool to assist in the control of the conflicts inherent to these functional areas and in the decision making of the managers. In this context, this research aims to analyze the impacts of marketing decisions on delivery performance and on the flexibility of the operations area in a food manufacturing company. These impacts were evaluated longitudinally through multiple linear regressions and artificial neural networks in a case study that includes the Internal Market and External Market models. The analysis of the marketing decisions on the delivery dimension regarding the Internal Market occurred through an artificial neural network. The results show that the decisions with the greatest impact on this operations area are related to the Place classification of the 4P's of marketing, followed by the Price and Product classifications. Additionally, it is verified that the formation of the sales channel significantly impacts delivery performance. In the analysis of the marketing decisions on the flexibility of the operations area with respect to the External Market model, the result is significant both for the artificial neural network and for the multiple linear regression. The evidences demonstrate that the decisions with the greatest impact on this operation area are included in the Product classification of the 4P's of marketing, followed by the Place and Price classifications.
Keywords: Operações; Desempenho; Entrega; Flexibilidade; Redes neurais artificiais; Regressão linear múltipla; Operations; Performance; Delivery; Flexibility; Artificial neural networks; Multiple linear regression; Marketing; ACCNPQ::Engenharias::Engenharia de Produção